Role of Prebiotics and Probiotics in Gut Microbiota Modulation and Human Health - Muhammad Syahrul Firmanyah; Sutrisno Adi Prayitno; Azril Akhmad Nur Islami (Academic Letters, 2025)
The human gut microbiota plays a vital role in maintaining overall health by regulating digestion, nutrient metabolism, immune function, and protection against pathogenic microorganisms. Imbalances in gut microbial composition, known as dysbiosis, have been strongly linked to the development of chronic diseases such as obesity, type 2 diabetes, inflammatory bowel disease, and cardiovascular disorders. Modern dietary patterns characterized by high intake of ultra-processed foods and low dietary fiber are major contributors to microbial dysbiosis. Prebiotics and probiotics have gained attention as functional food components capable of beneficially modulating gut microbiota composition and activity. Probiotics introduce beneficial microorganisms that enhance intestinal barrier function, suppress pathogens, and regulate immune responses, while prebiotics selectively stimulate microbial growth and promote short-chain fatty acid production. The synergistic use of prebiotics and probiotics supports gut integrity, immune balance, and metabolic health. Their integration into daily diets represents a promising strategy for preventive nutrition and long-term disease risk reduction